(untitled) - Graham., Jeffrey B. (New York, 1997)
Air Breathing Fishes: Evolution, Diversity, and Adaptation is unique in its coverage of the evolution of air-breathing, incongruously because it focuses exclusively on fish. This important and fascinating book, containing nine chapters that present the life history, ecology, and physiology of many air-breathing fishes, provides an exceptional overview of air-breathing biology.
Sinh lý Động vật Thủy sản hô hấp khí trời
Keywords: Human behavior,Cá thở không khí,Air-breathing fishes,Cá thở không khí,Air-breathing fishes; Hô hấp.,Respiration